Heterogeneity of high grade cervical intraepithelial neoplasia related to HPV16: Implications for natural history and management - Wentzensen, Nicolas (2012)
Factors associated with progression from cervical intraepithelial neoplasias (CIN) grade 2 and 3 to invasive cancer are not well understood; most CIN2 and CIN3 do not progress to cancer. Among carcinogenic HPV types, infections with HPV16 have the highest risk of progressing to cancer. We evaluated the heterogeneity of risk factors, lesion size, colposcopic impression, and colposcopic biopsy results in relation to HPV16 status among 627 women with CIN2 or CIN3 in women referred to colposcopy at the University of Oklahoma. Loop excision specimens were evaluated in 12 radial segments to estimate lesion size. The mean age at CIN3 was 27.7 years for HPV16-positive women (n=225) and 33.6 years for HPV16-negative women (n=104), respectively. The average lesion size did not differ by HPV16 status (p=0.83). Among HPV16-positive women with CIN3, lesions were significantly larger in women 30 years and older (p=0.03). Colposcopic impression was worse in women with HPV16 infections (p=0.009), but the detection of CIN3 at the preceding biopsy was not improved in HPV16-positive women. CIN3 is detected at the same lesion size, but at much younger age in women with HPV16 infections, suggesting faster growth. CIN2 lesion size in women without HPV16 peaks below 30 years and then decreases, suggesting frequent regression, while HPV16-related CIN2 is more likely to persist. Lesion size seems to be the most important determinant of colposcopy and biopsy performance. Genotyping for HPV16 in cervical cancer screening can improve risk stratification, but may pose challenges to finding small lesions in colposcopy.